THE METHOD OF AUTOMATED BUILDING OF DOMAIN ONTOLOGY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This article is devoted to the tasks of automating the construction of domain ontologies. In the beginning, the limitations and problems of constructing the ontology of the domain using the well-known methods are discussed. Next, a model of the domain ontology is proposed, which provides the ability to automatically build the ontological hierarchy, including the automatic synthesis of generalized concepts. Then, the article discusses the method of building an ontology based on the proposed model using machine learning, and discusses its capabilities and limitations.